Whither Reading in Malaysia: Confronting Reading Reluctancy Among Pre-University Students - Pandian, Ambigapathy; Ibrahim, Ab. Latif (Universiti Kebangsaan Malaysia, 1997)
It seems useful to begin this paper by providing an insight into the profile of three sample Malaysian readers that participated in this study on readership behavior.